Fictions of conversion : Jews, Christians, and cultures of change in early modern England - Shoulson, Jeffrey S. (University of Pennsylvania Press, 2013)
This book investigates the anxieties produced by the rapid and erratic religious, political, and cultural transformations in early modern England, which were often given shape in poetry, plays, and translations by the figure of the Jewish converso. The author argues that the vagaries of religious conversion were more readily negotiated when they were projected onto an alien identity - one of which the potential for transformation offered both promise and peril, but which could be kept distinct from the emerging identity of Englishness: the Jew.